EVALUASI PELAKSANAAN PROGRAM TRANSMIGRASI MODEL RING I DI DESA KARANGTENGAH KECAMATAN IMOGIRI KABUPATEN BANTUL - , DWI BAYU PRASETYA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The transmigration program of ring I model with the agricultural pattern in the Karangtengah village, Imogiri District Bantul regency, has been conducted since 2002 by the Office of Manpower and Transmigration Special Province of Yogyakarta. The determination Karangtengah Village as the location transmigration of ring I model is in order to increase the empowerment of communities in environmental and natural resource management and handling of refugee population in Bantul District transmigration through an integrated program which called ring I model. The objective of transmigration program with ring I model is to increase the family income and welfare of the migrants who come from diverse backgrounds, as well as exodant, displaced victims of natural disasters as well as local villagers of Karangtengah or from the outside Karangtengah village which is still in Bantul Regency. By objective of that program, the level of transmigrant family welfare used to measure the success of the program